2021 IEEE/ACM 43rd International Conference on Software Engineering: Software Engineering in Society (ICSE-SEIS) 2021
DOI: 10.1109/icse-seis52602.2021.00012
|View full text |Cite
|
Sign up to set email alerts
|

A First Look at Human Values-Violation in App Reviews

Abstract: Ubiquitous technologies such as mobile software applications (mobile apps) have a tremendous influence on the evolution of the social, cultural, economic, and political facets of life in society. Mobile apps fulfil many practical purposes for users including entertainment, transportation, financial management, etc. Given the ubiquity of mobile apps in the lives of individuals and the consequent effect of these technologies on society, it is essential to consider the relationship between human values and the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Shams et al [40] analysed 1,522 reviews from 29 Bangladeshi agricultural apps to understand both the desired and missing values that should be addressed in the development of such apps. Furthermore, Obie et al [31] introduced a dictionary-based natural language processing technique for detecting the violation of human values in app reviews. The result of their study showed that 26.5% of the analyzed 22,119 app reviews contained perceived violations of human values by the end-users.…”
Section: Background and Related Work 31 Human Values In Software Engi...mentioning
confidence: 99%
See 4 more Smart Citations
“…Shams et al [40] analysed 1,522 reviews from 29 Bangladeshi agricultural apps to understand both the desired and missing values that should be addressed in the development of such apps. Furthermore, Obie et al [31] introduced a dictionary-based natural language processing technique for detecting the violation of human values in app reviews. The result of their study showed that 26.5% of the analyzed 22,119 app reviews contained perceived violations of human values by the end-users.…”
Section: Background and Related Work 31 Human Values In Software Engi...mentioning
confidence: 99%
“…As important steps towards addressing the violation of the values of mobile apps users in society, Obie et al [31] proposed the mining of values requirements from rich data sources, the alignment of values between stakeholders in SE projects, and the adoption of critical technical practice in mobile SE. A recent study further contends that careful consideration of domain context in the design and application of values instruments should be made during values requirements gathering, as the hierarchy of end-users values may vary depending on the end-users domain context [32].…”
Section: Background and Related Work 31 Human Values In Software Engi...mentioning
confidence: 99%
See 3 more Smart Citations